The genomic distribution of histone H3K4me2 in spermatogonia is highly conserved in sperm†. Issue 6 (5th April 2019) - Lambrot, Romain; Siklenka, Keith; Lafleur, Christine; Kimmins, Sarah
Abstract: Environmental exposures can alter the long-term health and development of offspring. How this environmental information is transmitted via the germline remains unknown, but it is thought to involve epigenetic inheritance. We recently determined that genetic disruption of histone H3 di-methylation at lysine 4 (H3K4me2) in sperm alters gene expression in the embryo and negatively impacts development across generations. However, little is known regarding when in spermatogenesis H3K4me2 methylation is established, and whether specific regions bearing H3K4me2 resist the epigenome remodeling that occurs throughout spermatogenesis. Our objective was to determine what genomic regions bearing histone H3K4me2 in spermatogonia are also present in sperm. Methods: Using transgenic mice expressing Oct4 -GFP, we isolated an enriched spermatogonia population and performed ChIP-seq for H3K4me2, followed by downstream bioinformatics analysis. Using our epigenomic data and existing datasets, we compared the genomic distribution of H3K4me2 between spermatogonia and sperm. We also assessed the expression level of genes enriched in H3K4me2 in spermatogenic cell types and at specific embryonic developmental time-points. We observed that many regions of the sperm epigenome bearing H3K4me2 are already present in spermatogonia, suggesting an early establishment of this histone mark in spermatogenesis. Subsets of genes with a high enrichment in H3K4me2 in sperm are strongly expressed in spermatogenesis and others are associated with high gene expression during embryo development. These findings suggest that if epimutations in H3K4me2 are induced in spermatogonia they have the possibility to persist throughout spermatogenesis and may influence fertility by altering gene expression in spermatogenesis and in the embryo. Abstract : Histone methylation (H3K4me2) is highly conserved from spermatogonia to sperm and is associated with gene expression in spermatogenesis and embryo development.